The fecal hemoglobin concentration, age and sex test score: Development and external validation of a simple prediction tool for colorectal cancer detection in symptomatic patients. Issue 10 (6th March 2017) - Cubiella, Joaquín; Digby, Jayne; Rodríguez‐Alonso, Lorena; Vega, Pablo; Salve, María; Díaz‐Ondina, Marta; Strachan, Judith A.; Mowat, Craig; McDonald, Paula J.; Carey, Francis A.; Godber, Ian M.; Younes, Hakim Ben; et al.
Abstract : Prediction models for colorectal cancer (CRC) detection in symptomatic patients, based on easily obtainable variables such as fecal haemoglobin concentration (f‐Hb), age and sex, may simplify CRC diagnosis. We developed, and then externally validated, a multivariable prediction model, the FAST Score, with data from five diagnostic test accuracy studies that evaluated quantitative fecal immunochemical tests in symptomatic patients referred for colonoscopy. The diagnostic accuracy of the Score in derivation and validation cohorts was compared statistically with the area under the curve (AUC) and the Chi‐square test. 1, 572 and 3, 976 patients were examined in these cohorts, respectively. For CRC, the odds ratio (OR) of the variables included in the Score were: age (years): 1.03 (95% confidence intervals (CI): 1.02–1.05), male sex: 1.6 (95% CI: 1.1–2.3) and f‐Hb (0–<20 µg Hb/g feces): 2.0 (95% CI: 0.7–5.5), (20‐<200 µg Hb/g): 16.8 (95% CI: 6.6–42.0), ≥200 µg Hb/g: 65.7 (95% CI: 26.3–164.1). The AUC for CRC detection was 0.88 (95% CI: 0.85–0.90) in the derivation and 0.91 (95% CI: 0.90–093; p = 0.005) in the validation cohort. At the two Score thresholds with 90% (4.50) and 99% (2.12) sensitivity for CRC, the Score had equivalent sensitivity, although the specificity was higher in the validation cohort ( p < 0.001). Accordingly, the validation cohort was divided into three groups: high (21.4% of the cohort, positive predictive value—PPV: 21.7%), intermediate (59.8%, PPV: 0.9%) and low (18.8%, PPV: 0.0%) risk for CRC. The FAST Score is an easy to calculate prediction tool, highly accurate for CRC detection in symptomatic patients. Abstract : What's new? Lower gastrointestinal symptoms potentially indicative of colorectal cancer (CRC) are a common reason for physician visits. While the probability that any one of those symptoms is associated with CRC is low, identifying patients for further screening remains a challenge. Here, the possibility of improving CRC diagnostic accuracy and risk stratification was explored using a three‐variable FAST Score based on fecal hemoglobin concentration, age, and sex. Among symptomatic patients referred to colonoscopy, the FAST Score prediction model identified three risk groups, the lowest of which ruled out CRC. Threshold scores were sensitive across variables, including country, age, and sex.